AGRESIVITAS KOMUNITAS PUNK DI KOTA KEDIRI, PROVINSI JAWA TIMUR - Karomalloh, Ahmad Darojatun (Prodi Kesejahteraan Sosial Universitas Binawan, 2024)
: Social inequality can provoke jealousy and envy among the majority of the poor, which ultimately prompted the formation of punk community groups as a form of protest and resistance and criticism of the rich. Criticism and behavior from the punk community often lead to aggressive behaviors. The study aims to determine the level of aggressiveness of the punk community in Kediri, East Java Province, both in terms of physical aggression, verbal agresion, anger, and hostility. This research uses a quantitative approach with descriptive methods. The total number of respondents was 40 respondents with registration techniques in which members of the population took samples. Data collection techniques through questionnaires, observations, and documentation. The assessment in this study uses the Buss and Perry aggression scales. (Kuesioner Agresi). The results of the study showed that the punk community's aggressiveness in the city of Kediri in terms of physical aggression was in the middle category with a score of 1119 of the lowest score and the highest score was 360 and 1800. The aspects of verbal aggresión were in the medium category with the score of 676 of the lower score, and the top score was 200 and 1000. Based on the results of the study, it shows the level of aggressiveness of the punk community in Kediri City, East Java Province, especially in terms of physical, verbal aggression, anger, and hostility. Based on the findings, the researchers recommended the